(untitled) (Journal of the College of Basic Education, 2023)
The educational process is an original activity aimed at stimulating the learner’s motivation and facilitating learningIt includes a set of activities and decisions taken by (the teacher - the learner) in the situationEducation through attention to teaching methods and techniques and the organization of learning forms in the situationAn educational process through which learners interact for the purpose of achieving specific educational goals. It sure isThis is done through intentional design of the educational environment and its engineering (organization of educational experiences) in a mannerSpecific so as to lead to the achievement of intended education for learners and under the supervision of the teacher. Therefore, physical and psychological conditions that help the learner to interact actively must be providedWith the components of the educational environment designed for the educational situation in order to provide educational experiencesThe information, knowledge, technical skills, attitudes and values that he needs in proportion to his capabilitiesAnd his preparations in educational ways and methods that contribute to his sensory perceptions of the information he acquireseducational situation and then help him how to process this information and the process of retrieving itand employing them in new educational situations. Based on what we present, the researcher decided to establish her research problem by employingInquiry strategy (in an educational environment to organize information and methods of acquisition by the learnerAnd stored in his memory and methods of retrieval according to the requirements of the educational situation throughHis abilities and readiness to accept educational experiences (knowledge and skill) related to drawing and statementIts impact on the acquisition of technical skills and the enhancement of its positive role in how it is employed in achievementHis artistic work, such as perspective, still life, pictorial composition, artistic project.....and others.The aim of the current research is to reveal (the inquiry strategy and its impact on teaching arts).Therefore, the researcher set two sub-goals to achieve it